Nutrient intake among Samoan children aged 2–4 years in 2015. (3rd April 2018) - Choy, Courtney C.; Thompson, Avery A.; Soti-Ulberg, Christina; Naseri, Take; Reupena, Muagututia S.; Duckham, Rachel L.; Hawley, Nicola L.
Abstract: Background: Young children are particularly vulnerable to malnutrition as nutrition transition progresses. The aim of this study was to examine the adequacy of macro- and micronutrient intake among 2–4.99-year-old Samoan children. Methods: Child dietary intake was measured using a 117-item food frequency questionnaire (FFQ) with a 30-day reference period. Daily total energy and nutrient intake was calculated by multiplying the frequency of daily consumption by the nutrient content of a fixed, standard portion size. Adequacy of macro- and micronutrient intake was determined using age-specific US Dietary Guidelines. Results: Most children met or exceeded recommendations for carbohydrate, fat and protein intake. More than half of the sample were not meeting the Recommended Dietary Allowance (RDA) for calcium (59.0%), 44.6% were not meeting RDA for potassium and intake of vitamin A and E was inadequate among 25.9% and 25.6%, respectively. Eighty per cent of children exceeded the tolerable upper limit for sodium. Adequacy of intake varied by age and census region of residence. Conclusion: Since inadequate dietary micronutrient intake was more common among older children (4–4.99 years) and those in the rural region, intervention should be targeted at those groups.